David busch's canon eos 90d guide to digital photography - BUSCH, DAVID D. (The David Busch Camera Guide Series., 2020)
David Busch's Canon EOS 90D Guide to Digital Photography is your all-in-one comprehensive resource and reference for the advanced Canon EOS 90D camera. This upgraded 32.5 megapixel APS-C model features a 45-point autofocus system. The Dual Pixel CMOS hybrid autofocus brings lightning-fast phase detect AF to live view and high-definition movie modes, too. The 90D's metering system includes a 220,000-pixel RGB+Infrared sensor with Face Detection for accurate exposure control. The 90D has Wi-Fi/ Bluetooth connectivity to allow linking the camera to a computer and iOS or Android smart devices, and an improved swiveling touch screen LCD. With this book in hand, you can quickly apply all these advanced features to your digital photography, while boosting your creativity to take great photographs with your Canon EOS 90D. Filled with detailed how-to steps and full-color illustrations, David Busch's Canon EOS 90D Guide to Digital Photography covers all this upscale camera's features in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included is the handy 90D "roadmap," an easy-to-use visual guide to the camera's features and controls. Learn when to use each option and, more importantly, when not to use them, by following the author's recommended settings for every menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera's capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Canon EOS 90D today.